2003
DOI: 10.1074/jbc.m209319200
|View full text |Cite
|
Sign up to set email alerts
|

Diethylstilbestrol Induces Rat Spermatogenic Cell Apoptosis in Vivo through Increased Expression of Spermatogenic Cell Fas/FasL System

Abstract: The significant role that estrogens play in spermatogenesis has opened up an exciting area of research in male reproductive biology. The realization that estrogens are essential for proper maintenance of spermatogenesis, as well as growing evidence pointing to the deleterious effects of estrogen-like chemicals on male reproductive health, has made it imperative to dissect the role estrogens play in the male. Using a model estrogen, diethylstilbestrol (DES), to induce spermatogenic cell apoptosis in vivo in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 50 publications
7
82
1
Order By: Relevance
“…Previous studies reported that exposure to non-physiological concentrations of estrogen, testosterone, and estrogenlike chemicals could stimulate the apoptotic pathway in animal germinal cells (Zhou et al 2001, Kim et al 2003, Nair & Shaha 2003, Jung et al 2004, Mishra & Shaha 2005, and cause DNA damage in human sperm (Anderson et al 2003). These reports support the correlations we observed for the European men, e.g.…”
Section: Xenobiotic-induced Receptor Activity Issuessupporting
confidence: 82%
“…Previous studies reported that exposure to non-physiological concentrations of estrogen, testosterone, and estrogenlike chemicals could stimulate the apoptotic pathway in animal germinal cells (Zhou et al 2001, Kim et al 2003, Nair & Shaha 2003, Jung et al 2004, Mishra & Shaha 2005, and cause DNA damage in human sperm (Anderson et al 2003). These reports support the correlations we observed for the European men, e.g.…”
Section: Xenobiotic-induced Receptor Activity Issuessupporting
confidence: 82%
“…In the GO classification, "apoptotic program" is a subcategory of "cell death" and refers to a form of programmed cell death. It has been reported that exposure to DES induces germinal cell apoptosis in male rodents (Nonclercq et al, 1996;Nair and Shaha, 2003;Ma et al, 2008); however, our results suggest that DES provides Leydig cells with an intracellular environment in which it is difficult to trigger apoptosis. Meanwhile, "DNA repair" is a subcategory of "DNA metabolism," which is the high-ranked GO term decreased in the DES-treated cells.…”
Section: Discussioncontrasting
confidence: 54%
“…The administration of DES to newborn or mature rats has been reported to increase germ cell apoptosis (Atanassova et al, 2000;Nair and Shaha, 2003). On the other hand, it has been reported that the administration of DES to adult rats does not influence spermatogenesis or sperm morphology (Goyal et al, 2001), and that DES administration increases FSH levels, promoting spermatogenesis (Atanassova et al, 1999).…”
Section: Discussionmentioning
confidence: 99%